Synthetic polymers and their potential as genetic materials. (27th December 2012) - Pinheiro, Vitor B.; Loakes, David; Holliger, Philipp
Abstract DNA and RNA are the only known natural genetic materials. Systematic modification of each of their chemical building blocks (nucleobase, sugar, and phosphate) has enabled the study of the key properties that make those nucleic acids genetic materials. All three moieties contribute to replication and, significantly, all three moieties can be replaced by synthetic analogs without loss of function. Synthetic nucleic acid polymers capable of storing and propagating information not only expand the central dogma, but also highlight that DNA and RNA are not unique chemical solutions for genetic information storage. By considering replication as a question of information transfer, we propose that any polymer that can be replicated could serve as a genetic material. Editor's suggested further reading in BioEssays Xenobiology: A new form of life as the ultimate biosafety tool Abstract